Role of Extracellular Vesicles in Substance Abuse and HIV-Related Neurological Pathologies - Odegaard, Katherine E.; Chand, Subhash; Wheeler, Sydney; Tiwari, Sneham; Flores, Adrian; Hernandez, Jordan; Savine, Mason; Gowen, Austin; Pendyala, Gurudutt; Yelamanchili, Sowmya V. (International journal of molecular sciences, 2020)
Extracellular vesicles (EVs) are a broad, heterogeneous class of membranous lipid-bilayer vesicles that facilitate intercellular communication throughout the body. As important carriers of various types of cargo, including proteins, lipids, DNA fragments, and a variety of small noncoding RNAs, including miRNAs, mRNAs, and siRNAs, EVs may play an important role in the development of addiction and other neurological pathologies, particularly those related to HIV. In this review, we summarize the findings of EV studies in the context of methamphetamine (METH), cocaine, nicotine, opioid, and alcohol use disorders, highlighting important EV cargoes that may contribute to addiction. Additionally, as HIV and substance abuse are often comorbid, we discuss the potential role of EVs in the intersection of substance abuse and HIV. Taken together, the studies presented in this comprehensive review shed light on the potential role of EVs in the exacerbation of substance use and HIV. As a subject of growing interest, EVs may continue to provide information about mechanisms and pathogenesis in substance use disorders and CNS pathologies, perhaps allowing for exploration into potential therapeutic options.